Mass absorption cross-section and absorption enhancement from long term black and elemental carbon measurements: A rural background station in Central Europe - Mbengue, Saliou; Zikova, Nadezda; Schwarz, Jaroslav; Vodička, Petr; Šmejkalová, Adéla Holubová; Holoubek, Ivan (The Science of the total environment, 2021)
Black carbon (BC) is a dominant aerosol light absorber, and its brown carbon (BrC) coating can enhance absorption and lead to uncertainties concerning the radiative forcing estimation. This study investigates the mass absorption cross-section of equivalent BC (MACeBC) during a long-term field measurement (2013-2017) at a rural Central European site. The MAC enhancement factor (Eabs) and the contribution of BrC coatings to the absorption coefficient (Babs) were estimated by combining different approaches. The annual mean Babs and MACeBC values decreased slightly over the measurement period associated with change in the submicron aerosol size distribution. Regardless of the wavelength, Babs exhibited clear seasonal and diurnal variations, with higher values in winter when a higher absorption Ångström exponent (1.4) was observed due to the local biomass burning (BB). In contrast, MACeBC did not have a distinct temporal trend at 600 nm (7.84 ± 2.79 m2 g-1), while it showed a seasonal trend at 370 nm with higher values in winter (15.64 ± 4.77 m2 g-1). During this season, Eabs_660 was 1.18 ± 0.27 and did not exhibit any clear wavelength dependence, despite the influence of BB. During the study period, BrC-attributed absorption was observed in 31% of the samples, with a contribution of up to 40% of total Babs. In summer, the Eabs_660 increased to 1.59 ± 0.60, when a larger BC coating could be formed by secondary aerosol fractions. During this season, MACeBC_660 and Eabs_660 showed comparable source profiles that were mainly associated with aged air masses over central Europe, thereby supporting the fact that characteristics of coating materials formed during atmospheric aging are a major factor driving the MACeBC_660 measured at the regional background site. Further field investigations of the composition of BC coatings would help to better understand and estimate uncertainties related to the radiative effect of aerosols.
Keywords: monitorování životního prostředí; látky znečišťující vzduch; Aerosols; Aerosol light absorption; Elemental carbon; Black carbon; Carbon; Environmental Monitoring; MAC; Absorption enhancement; Air Pollutants; Brown carbon; Evropa; uhlík; Europe; aerosoly